An enhanced microbial water quality monitoring design using a novel area prioritization approach to site selection - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Thesis (PhD (Water Resource Management))--University of Pretoria, 2005.